Policing Services With Mentally Ill People: Developing Greater Understanding and Best Practice. (3rd August 2012) - Ogloff, James RP; Thomas, Stuart DM; Luebbers, Stefan; Baksheev, Gennady; Elliott, Irina; Godfredson, Joel; Kesic, Dragana; Short, Tamsin; Martin, Trish; Warren, Lisa; Clough, Jonathan; Mullen, Paul E; et al.
<x xml:space="preserve">Abstract</x> Although it is now well known that there is a disproportionate number of people with mental illnesses in the criminal justice system, surprising little attention has been paid to the challenges faced by policing people with mental illnesses in the community. This article provides an overview of some of the key findings from a programme of research undertaken in Victoria to further understand and develop a best practice model at this interface. The areas covered will include the prevalence of psychiatric symptoms and mental illnesses among police cell detainees; the existing knowledge base and attitudes of police towards mentally ill people; the relationship between mental illness and offending; the frequency and nature of police apprehensions of mentally ill people under the Mental Health Act; the association among mental disorder, police shootings, and other injuries to people as a result of these encounters; and police interactions with victims of crime. The work highlights the need for ongoing improvements in policing people with mental illnesses, and particularly the need for improved inter‐agency practices for dealing with them.